2006
DOI: 10.22358/jafs/66835/2007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of production system on performance traits, carcass and meat quality in Brown Swiss young cattle

Abstract: Performance, carcass and meat quality were assessed in 3 groups of Brown Swiss male calves, all of them suckled by their dams: groups M200 and M250 were exclusively milk-fed and slaughtered at 200 or 250 kg, respectively, and G400 group was supplemented with grain and slaughtered at 400 kg after a short finishing period. Increasing weight in milk-fed animals led to an increase in dressing percentage and conformation score, and a decrease in muscle content with an increase in dissectible fat in the rib, with no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…For the same slaughter weight, Cerdeño et al [ 50 ] did not show significant differences on the conformation score and dressing% of calves when different rearing managements were applied during the pre-weaning period. However, if the calves were slaughtered higher, the conformation score and the dressing% of their carcass were improved [ 51 ]. The rearing management applied during the pre-weaning period could have an impact on the carcass traits.…”
Section: Discussionmentioning
confidence: 99%
“…For the same slaughter weight, Cerdeño et al [ 50 ] did not show significant differences on the conformation score and dressing% of calves when different rearing managements were applied during the pre-weaning period. However, if the calves were slaughtered higher, the conformation score and the dressing% of their carcass were improved [ 51 ]. The rearing management applied during the pre-weaning period could have an impact on the carcass traits.…”
Section: Discussionmentioning
confidence: 99%
“…As our results, in the study of Gondeková (2011) bulls reached better evaluation in all the observed parameters than cows but only differences in odour and tenderness were statistically significant. Also, Cerdeno et al (2006), and Faucitano et al (2008) determined better results in bulls than cows. However, observed better sensory evaluation in cows than bulls.…”
Section: Resultsmentioning
confidence: 86%